Comparison of mechanical properties between different stainless steel archwires - Abu Bakar, Noraini; McDonald, Fraser; Sheriff, Martyn; Tan, Lawrence (Oxford University Press, 2013)
AIM: The Damon system recommends the use of revolutionary, high-technology Damon edgewise wires [0.019 0.025 inch stainless steel (SS)] for major mechanics and finishing. No study has been carried out to compare this relatively new Damon SS archwire to other popular SS archwires. The aim of this study was to compare the mechanical properties of Damon 0.019 0.025 inch SS archwires with Standard Ormco and 3M 0.019 0.025 inch SS archwires.MATERIALS AND METHOD: Thirty preformed archwires of each type (Standard Ormco, 3M and Damon) were tested in the as-received condition. Tensile tests were performed on an Instron Universal Testing Machine. Data were obtained for maximum load, 0.1 per cent yield strength and Automatic/Young’s modulus. RESULTS: For maximum load, there was no difference between Damon (mean: 659.8 ± 26.6 N) and 3M (mean: 668.4 ± 9.1 N) archwires, but both were statistically superior to Standard Ormco (mean: 611.9 ± 23.2 N). With respect to automatic modulus, Damon (mean: 41786.0 ± 5104.2 MPa) was statistically inferior to both Standard Ormco (mean: 47318.2 ± 6106.2 MPa) and 3M (mean: 49897.6 ± 3286.1 MPa) wires. For the 0.1 per cent yield strength, there was no difference between Damon (mean: 2150.1 ± 88.6 MPa) and 3M (mean: 2178.8 ± 29.6 MPa), but both were statistically superior to the Standard Ormco archwires (mean: 1990.8 ± 74.5 MPa). With regard to the Young’s modulus, Damon (mean: 40598.3 ± 5077.4 MPa) was statistically inferior to both Standard Ormco (mean: 44910.9 ± 5463.4 MPa) and 3M (mean: 47500.7 ± 3431.6 MPa). CONCLUSION Damon 0.019 0.025 inch SS archwires were shown to be similar to 3M in maximum load and 0.1 per cent yield strength. As for Young’s and Automatic Modulus, Damon was statistically inferior to 3M and Standard Ormco. 3M was superior in all parameters.